Plan estratégico y su relación con la reincorporación a la sociedad de las (ppl) personas privadas de libertad género femenino del centro de rehabilitación, Cantón Quevedo, periodo 2013-2017 - Cayo Osorio, Sergio Gabriel (2014)
This research was conducted with the purpose of improving the current and future situation of Persons Deprived of Liberty, performing a strategic plan properly structured based on the problems identified Social Rehabilitation Center Quevedo. This paper covers basic criteria and planning concepts linked with must have a strategic is summed. Reviewing relevant aspects to be considered for proper planning, for which proposed projects whose activities should be run as scheduled to achieve the desired results in the stipulated time. The data collection was undertaken by applying survey the detainees Rehabilitation Center of Canton Quevedo which consists of 12 questions. The results obtained show that there is a deficit in planning the Social Rehabilitation Center Quevedo, finding that 58 % of respondents unaware of a Strategic Plan for the reintegration into society of person deprived of liberty. Appropriate methods and were designed, which once analyzed, contributed to hypothesis testing, for issuing the respective conclusions and recommendations based on the study and applied.